2012
DOI: 10.1182/blood-2012-06-435297
|View full text |Cite
|
Sign up to set email alerts
|

STAT3 mutations unify the pathogenesis of chronic lymphoproliferative disorders of NK cells and T-cell large granular lymphocyte leukemia

Abstract: Chronic lymphoproliferative disorders of natural killer cells (CLPD-NKs

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

14
343
9
2

Year Published

2015
2015
2019
2019

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 362 publications
(382 citation statements)
references
References 35 publications
14
343
9
2
Order By: Relevance
“…However, evidence of increased STAT3 activity has been shown in patients meeting strict criteria for LGL leukemia with both wild-type and mutated STAT3. 6-8 Jerez et al 7 showed that both cases of STAT3-mutated and wild-type LGL leukemia produce increased amounts of pSTAT3 and both types showed similar profiles of dysregulation in genes involved in apoptosis. Thus, other mechanisms of increased STAT3 activity in LGL leukemia may exist but likely confer similar features.…”
mentioning
confidence: 99%
See 4 more Smart Citations
“…However, evidence of increased STAT3 activity has been shown in patients meeting strict criteria for LGL leukemia with both wild-type and mutated STAT3. 6-8 Jerez et al 7 showed that both cases of STAT3-mutated and wild-type LGL leukemia produce increased amounts of pSTAT3 and both types showed similar profiles of dysregulation in genes involved in apoptosis. Thus, other mechanisms of increased STAT3 activity in LGL leukemia may exist but likely confer similar features.…”
mentioning
confidence: 99%
“…STAT3 mutation has been demonstrated in both T-cell and natural killer (NK) cell-derived cases, and is associated with increased phosphorylated STAT3 protein (pSTAT3) which can be visualized by immunohistochemistry (IHC). 6,7 Furthermore, increased pSTAT3 and STAT3 activity has been demonstrated in both STAT3-mutated and wild-type LGL leukemia when strict diagnostic criteria are used. 7 In order to better understand this rare disease, we used strict diagnostic criteria to identify seven patients who developed LGL leukemia following HSCT and used IHC to assess for nuclear localization of pSTAT3 in leukemic cells.…”
mentioning
confidence: 99%
See 3 more Smart Citations